Enacting a rational actor: Roboadvisors and the algorithmic performance of ideal types. Issue 4 (1st October 2020) - Hayes, Adam
Abstract: Weber famously invoked 'ideal types' as an analytic device with which to measure empirical reality against some hyper-rational fabrication. Case in point: non-professional (lay) investors appear to be the antithesis of rational economic man. They have been cast as less-informed, less-skilled, and less-knowledgeable than professional market practitioners, and with ample evidence that they tend to lose money in the market as a result. This study builds the case that a new class of algorithmic financial advisor, commonly known as 'roboadvisors', enacts lay investors as rational market actors. This is achieved through algorithmic devotion to modern portfolio theory (MPT), which the roboadvisors embody, automate and perform, conjuring some version of homo economicus into existence. Through this example, I show how Weberian ideal types and the particular kind of rational action associated with them (e.g. the ideal type investor) become the very empirical reality they were intended to be a foil to – accomplished through the technological articulation of financial models, even in the hands of ordinary individuals.